Systematic Review of Electromyography for Assessing Physiotherapy Outcomes in Children with Cerebral Palsy - Rendranandini, Widya; widodo, agus (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Cerebral palsy is a disorder that affects the movement and posture of the brain of a developing fetus or baby. The prevalence is around 1-4 per 1000 live births globally, with 9 birth cases in Indonesia. CP children experience various sensory and motor disorders. Various interventions require a tool that can reliably detect the success of therapy. Electromyography (EMG) is an objective method for understanding muscle activity, helps in determining the muscles involved in movement, and provides related information about muscle activity in response to therapy. This study aimed to determine EMG in evaluating the results of therapy. Subjects and Method: A literature search was carried out using 2 databases, namely PubMed and Google Scholar regarding the use of EMG to assess or analyze physiotherapy interventions given to children with CP from the period 2018 - 2023. Using PRISMA as a writing rule. Results: 8 studies described the use of EMG in physiotherapy, 3 articles looked at muscle activity, 3 articles assessed muscle activation, 1 article assessed spastic responses, and 1 article looked at motor neuron excitatory pools. Conclusion: EMG helps physiotherapy in seeing muscle activity, muscle activation, seeing the spastic response of a muscle, and measuring the collection of excitatory motor neurons.